Analyze extreme wind speed in peninsular Malaysia - Aisyatul Azlin, Sitam (2014)
The focus of the study is to analyze the maximum wind speed, maximum gust speed and damage to buildings cause of extreme wind in Peninsular Malaysia. Natural wind flow is one of the most effective methods to help achieve energy savings in large cities, particularly under tropical climate such as Malaysia. The weather in Malaysia is characterized by four monsoon regime of the southwest monsoon, northeast monsoon and two shorter than the monsoon season. For this study, data of wind velocity in a weather station in Malaysia obtained from the Department of Meteorology and considered in the environmental assessment of the wind. The maximum wind speed 6.68 m/s in July 2008, the maximum wind velocity and wind maximum in 2003-2013 to station in Penang. From these data, according to the Beaufort scale of wind is fresh Breeze and the maximum gust speed of 6.31 m/s in January 2005, the maximum wind velocity and wind maximum in 2003-2013 to station in Malacca. From these data, according to the Beaufort scale of wind is fresh Breeze. From this data, according to the Beaufort scale of wind is fresh Breeze. This study results are compared in Table 2.1 in the Beaufort scale. The damage of buildings caused by wind conditions often occur and are relevant for the design of the building was a storm, and the wind velocity at a specific height above the ground. This condition is generally associated with one of these situations including tornado, storm, wind conditions specific local wind from the geographical and climatic conditions and the latter is odd local wind conditions resulting from sea level. The effect of wind on the building can be classed into several parts due to certain criteria; the wind was in the know of direct pressure between the outer wall, the outer wall suction, pressure on the surface of the roof, the whole of the building and more. The effect of this can be solved with several conditions including a strong connection, a secure site, and the selection of appropriate materials, orderly arrangement of buildings and failure modes and prevention. Wind is moving air with a specific mass (density or weight) and it moves in a certain direction with a certain velocity. Whenthis moving air collides with an object, it will produce a number of effects that result in a force on the object